Mekong Dreaming : Life and Death along a Changing River - Johnson, Andrew Alan (Book collections on Project MUSE., 2020)
"MEKONG DREAMING is an ethnography of the changing relationship between the Mekong River and the residents of Ban Beuk, a small town on the border of Thailand and Laos. In recent years, the Greater Mekong Sub-region has undergone vast infrastructural development, ranging from the construction of high-speed trains to several major river dams. These infrastructure projects have affected the river and those who rely on it; for example, fishing patterns have changed as the flow of water from the dam is manipulated. In this book, anthropologist Andrew Alan Johnson centers the intangible and invisible effects of developing infrastructure, and examines the construction's effect on inhuman elements such as spirits, ghosts, and dreams. Building upon the ontological turn in anthropology, Johnson argues for a world along the Mekong river in which human and inhuman elements are entangled, and where reality is opaque and only partially knowable. For Johnson, the key to understanding these relationships is through what he calls "distant potency." Distance, for Johnson, is physical-in the sense that the residents of Ban Beuk must contend with a dam controller miles away, whom they will never meet-as well as epistemological, as it implies a reality that is only partially accessible. But rather than distance having a weakening effect, Johnson argues that distance creates a potency of power by marking that which is distant-and therefore foreign-as powerful. What emerges, then, is a world along the Mekong in which distant yet powerful infrastructure alters what is known and knowable for residents of Ban Beuk living in the wake of regional development. The introduction of the book introduces the main theoretical concepts of distance and potency, as well as a grounding in ontology-based anthropology. Chapter 2 situates Ban Beuk as a border town between Thailand and Laos, and positions the town's "borderness" as a liminality that enables ebbs and flows of power. Chapter 3 focuses on the Mekong river itself, and the effects of the dam and hydropower on the water, fish, humans, and nonhuman subjects who reside along its banks. Chapter 4 investigates the relationship between Ban Beuk and migrant labor, and positions the migrant as a figure through which one can understand power and potency as experienced along the Mekong. Chapter 5 explores ghosts and spirits who have either arrived or disappeared following hydropower development. The last chapter returns to the theoretical stakes of the book, and theorizes the "inhuman" as a subject position whose location is unimaginable. This book will be of interest to students and scholars of anthropology and Southeast Asia"--